2002
DOI: 10.1002/app.11302
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and performance of high‐impact polystyrene (HIPS)/nano‐TiO2 nanocomposites

Abstract: High-impact polystyrene (HIPS)/nano-TiO 2 nanocomposites were prepared by surface pretreatment of nano-TiO 2 with special structure dispersing agent (TAS) and master batch manufacturing technology. The results show that when the nano-TiO 2 content is 2%, the notched impact strength, tensile strength, and elastic modulus of HIPS/ nano-TiO 2 nanocomposites increased to a maximum. This result indicates that nano-TiO 2 has both toughening and reinforcing effects on HIPS. The heat-deflection temperature and flame-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
62
0
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(67 citation statements)
references
References 13 publications
4
62
0
1
Order By: Relevance
“…This means that it was relatively hard to initiate fracture on the 5 wt.% zeolite/HDPE composite but once fracture initiated, the pure HDPE was more resistant than 5 wt.% zeolite/HDPE composite against fracture propagation. These fracture toughness characteristics are similar to the results of the research conducted by Zhang et al [25,26]. They reported that the impact strength increased with filler content increased up to about 6 wt.% but decreased with filler content increased further.…”
Section: Resultssupporting
confidence: 89%
“…This means that it was relatively hard to initiate fracture on the 5 wt.% zeolite/HDPE composite but once fracture initiated, the pure HDPE was more resistant than 5 wt.% zeolite/HDPE composite against fracture propagation. These fracture toughness characteristics are similar to the results of the research conducted by Zhang et al [25,26]. They reported that the impact strength increased with filler content increased up to about 6 wt.% but decreased with filler content increased further.…”
Section: Resultssupporting
confidence: 89%
“…Because the inherent hydrophilicity of PMMA is limited, the hydrophilicity of the in situ PVDF/PMMA blend is not much higher. However, inorganic materials (like TiO 2 and SiO 2 ) always have high hydrophilicities due to their high surface energies [21,22]. Therefore, in the work described in this paper, inorganic TiO 2 and SiO 2 nanoparticles were introduced during the in situ polymerization of MMA in PVDF in order to improve the hydrophilicity of PVDF.…”
Section: Introductionmentioning
confidence: 99%
“…[3] Inorganic compounds that restrict pathogens are usually supplemented to the polymers by melt mixing or other processes in the ultra-fine phase dimension of dispersion behavior. [4] of nanoscale filler in the polymer medium. Transmission electron microscopy has been used to observe this process at high magnification.…”
Section: Introductionmentioning
confidence: 99%